Peningkatan Motivasi Belajar Matematika bagi Siswa SMA Melalui Permainan Edukasi: Increasing Motivation to Learn Mathematics for High School Students Through Educational Games - yundari yundari; Nilamsari Kusumastuti; Bayu Prihandono; Helmi; Mariatul Kiftiah; Nur’ainul Miftahul Huda; Yudhi; Meliana Pasaribu; Fransiskus Fran; Evi Noviani (Komatika: Jurnal Pengabdian Kepada Masyarakat, 2024)
Understanding the basic concepts of mathematics is the key to learning and applying mathematics in other disciplines. Many students today only rely on memorizing formulas without understanding mathematics concepts. One way to be introduced so that students do not just memorize and think math is boring is educational games. Community service conducted by lecturers of the Mathematics Study Program FMIPA Tanjungpura University to students of SMA Negeri 1 Singkawang West Kalimantan amis to increase motivation to learn matematis through educational games. The method used was in the form of educational seminars on educational games in the field of mathematics and exhibitions of mathematical teaching aids. Students are given some basic math problems that can be solved through games. Some concepts of algebra, geometry, and statistics were given as examples in applying educational games. In addition, some props to facilitate math solutions were also given, such as trigonometry, geometry, and algebraic calculation props. One of the results obtained is that students feel that activities like this need to be done so that student's interest in mathematics increases. Furthermore, this activity also gives a better understanding of the basic concepts of mathematics to other disciplines